-9u-5+6=19

Simple and best practice solution for -9u-5+6=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9u-5+6=19 equation:


Simplifying
-9u + -5 + 6 = 19

Reorder the terms:
-5 + 6 + -9u = 19

Combine like terms: -5 + 6 = 1
1 + -9u = 19

Solving
1 + -9u = 19

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -9u = 19 + -1

Combine like terms: 1 + -1 = 0
0 + -9u = 19 + -1
-9u = 19 + -1

Combine like terms: 19 + -1 = 18
-9u = 18

Divide each side by '-9'.
u = -2

Simplifying
u = -2

See similar equations:

| -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 | | 7a^2+49a+60=0 | | (sin(x))*2=116 | | 1x+-7=2x+-6 | | (sin(x))2=116 | | 4x^3-33x-30x=0 | | -3(2y-2)-y=-2(y-2) | | 4v-(6v+8)=8v-38 | | 88+1.5h=94-2h | | 9(3x+12x)= | | (x+3.3)m=28 | | 1x+-7=x-2x+-6 | | 2x+4=6+4 | | 5x-4x+4=-2+4x+9 | | 10g=-16+6(8g+9) | | 3(x+7)=7x+7-4x+14 | | v+2.9=4.71 | | 4n-3=2n+2 | | -4(2y-4)-y=-2(y-5) | | 0.01x+0.10(200-x)=0.41x | | 12(x+1)=3(x+28) |

Equations solver categories